Pharmacokinetics and metabolism of racemic 2',3'-dideoxy-5-fluoro-3'-thiacytidine in rhesus monkeys. - Schinazi, R F (1992)
2',3'-Dideoxy-5-fluoro-3'-thiacytidine (FTC) is a nucleoside analog that selectively inhibits human immunodeficiency and hepatitis B viruses in vitro. In this study, the preclinical pharmacokinetics of racemic FTC in rhesus monkeys following intravenous and oral administration were characterized. The terminal half-life of FTC was independent of the route of administration and averaged 1.34 +/- 0.18 h (mean +/- standard deviation). Total clearance of FTC was moderate to high, averaging 1.49 +/- 0.24 liters/h/kg. Qualitative assessment of urine samples suggests that renal excretion of unchanged FTC was the major route of elimination of the nucleoside. The compound was also eliminated by metabolism and the deaminated biotransformation product 2,3'-dideoxy-5-fluoro-3'-thiauridine (FTU) was detected in serum and urine. This metabolite has no antiviral activity in human lymphocytes and liver cells. FTC and the metabolite FTU were conjugated, to a minor extent yielding the corresponding glucuronides. No 5-fluorouracil was detected in serum or urine. This is consistent with chromatographic studies using a chiral column that indicated that when racemic FTC is treated with cellular cytidine-deoxycytidine deaminase, the D-(+)-enantiomer of FTC is slowly deaminated to D-(+)-FTU, whereas the L-(-)-enantiomer is essentially resistant to this enzyme. The steady-state volume of distribution of FTC in serum averaged 2.23 +/- 0.42 liters/kg, and the nucleoside analog was distributed into the cerebrospinal fluid, which suggests that this drug penetrated the blood-brain barrier. Absorption of FTC after oral administration was rapid, with bioavailability averaging 73 +/- 6%. Taken together, the results indicate that the unusual L-(-)-enantiomer of FTC should be evaluated further in rhesus monkeys prior to determination of whether this compound is useful for treatment of human immunodeficiency and hepatitis B virus infections.